2011
DOI: 10.3109/17482941.2011.581292
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital treatment of STEMI patients. A scientific statement of the Working Group Acute Cardiac Care of the European Society of Cardiology

Abstract: key-words: ST elevation myocardial infarction -acute coronary syndromes -acute cardiac carepre-hospital -emergency medical service -networks 2 IntroductionOptimal treatment for ST-elevation myocardial infarction (STEMI) is based on a reperfusion strategy employing either primary percutaneous coronary intervention (PPCI) or thrombolytic therapy (TT). A sizable proportion of STEMI patients are not reperfused, time delays are frequently unacceptable 1 and very few patients receive all the guideline-recommended th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 127 publications
0
24
0
3
Order By: Relevance
“…After obtaining written informed consent, we randomly divided these patients into two groups according to the administration of ticagrelor or clopidogrel during the therapy, 54 patients in the ticagrelor group (treatment group: Load dosage of 180 mg, maintenance dosage of 90 mg/time, twice a day) and 53 patients in the clopidogrel group (control group: Load dosage of 300 mg, maintenance dosage of 75 mg/time, once a day), and performed follow-up by telephone for 30 days after the discharge of the enrolled patients. All the cases corresponded with the definition of acute myocardial infarction of the Third Global Seminar of ESC/ACCF/AHA/WHF and the Diagnostic Criteria of Acute Myocardial Infarction stipulated by the Chinese Society of Cardiology (2010) (3,4). Exclusion criteria were: i) Patients who would have severe adverse reaction to ticagrelor or were resistant to clopidogrel; ii) patients with a history of myocardial infarction or with other heart diseases and/or severe heart failure (NYHA III or IV); iii) patients who had severe hepatic or renal dysfunction; iv) patients who had history of PCI or coronary artery bypass grafting (CABG) or had accepted other types of surgeries or been injured recently; v) patients with endocrine diseases such as diabetes, and immune system diseases such as acute or chronic infections, digestive tract infections, hematological diseases, malignant tumors, rheumatic disease of connective tissues; vi) patients with severe hypertension without any drug controls, cerebrovascular diseases or peripheral vascular disease; and vii) patients who had any conditions deemed inappropriate by researchers for inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%
“…After obtaining written informed consent, we randomly divided these patients into two groups according to the administration of ticagrelor or clopidogrel during the therapy, 54 patients in the ticagrelor group (treatment group: Load dosage of 180 mg, maintenance dosage of 90 mg/time, twice a day) and 53 patients in the clopidogrel group (control group: Load dosage of 300 mg, maintenance dosage of 75 mg/time, once a day), and performed follow-up by telephone for 30 days after the discharge of the enrolled patients. All the cases corresponded with the definition of acute myocardial infarction of the Third Global Seminar of ESC/ACCF/AHA/WHF and the Diagnostic Criteria of Acute Myocardial Infarction stipulated by the Chinese Society of Cardiology (2010) (3,4). Exclusion criteria were: i) Patients who would have severe adverse reaction to ticagrelor or were resistant to clopidogrel; ii) patients with a history of myocardial infarction or with other heart diseases and/or severe heart failure (NYHA III or IV); iii) patients who had severe hepatic or renal dysfunction; iv) patients who had history of PCI or coronary artery bypass grafting (CABG) or had accepted other types of surgeries or been injured recently; v) patients with endocrine diseases such as diabetes, and immune system diseases such as acute or chronic infections, digestive tract infections, hematological diseases, malignant tumors, rheumatic disease of connective tissues; vi) patients with severe hypertension without any drug controls, cerebrovascular diseases or peripheral vascular disease; and vii) patients who had any conditions deemed inappropriate by researchers for inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced prehospital management by emergency medical services (EMS) plays a crucial role in facilitating access to care and reducing mortality rates for STEMI patients 711. Studies have shown that transport by EMS is associated with quicker treatment, including shorter symptom-onset-to-arrival time and door-to-reperfusion time, when compared to private transport 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…In our series, with a lower mean age than the above studies, complete AV block was present in 2.4% of patients. This group, along with the nearly 6% of patients with severe bradycardia, require advanced clinical management in the field during the prehospital phase 8 9 22…”
Section: Discussionmentioning
confidence: 99%